Some Approaches for Light and Color on the Surface of Mars - Manuel Melgosa; Javier Hernández-Andrés; Manuel Sánchez-Marañón; Javier Cuadros; Álvaro Vicente-Retortillo (Applied Sciences)
We analyzed the main colorimetric characteristics of lights on Mars’ surface from 3139 total spectral irradiances provided by the COMIMART model (J. Space Weather Space Clim. 5, A33, 2015), modifying the parameters of ‘solar zenith angle’ and ‘opacity’, related to the time of day and the amount of dust in the atmosphere of Mars, respectively. Lights on Mars’ surface have chromaticities that are mainly located below the Planckian locus, correlated color temperature in the range of 2333 K–5868 K, and CIE 2017 color fidelity indices above 93. For the 24 samples in the X-Rite ColorChecker® and an extreme dust opacity change from 0.1 to 8.1 in the atmosphere, the average color inconstancy generated by the change in Mars’ light using the chromatic adaptation transform CIECAT16 was about 5 and 8 CIELAB units for solar zenith angles of 0° and 72°, respectively. We propose a method to compute total spectral irradiances on the surface of Mars from a selected value of correlated color temperature in the range of 2333 K–5868 K. This method is analogous to the one currently adopted by the International Commission on Illumination to compute daylight illuminants on the surface of Earth (CIE 015:2018, clause 4.1.2). The average accuracy of 3139 reconstructed total spectral irradiances using the proposed method was 0.9999558 using GFC (J. Opt. Soc. Am. A 14, 1007–1014, 1997) and 0.0009 ΔEu′v′ units, a value just below noticeable chromaticity differences perceptible by human observers at 50% probability. Total spectral irradiances proposed by Barnes for five correlated temperatures agreed with those obtained from the current proposed method: on the average, GFC = 0.9979521 and 0.0023 ΔE′v′ units.